PENGENDALI ALIRAN GAS HIDROGEN PADA MASUKAN DAN KELUARAN PROTON EXCHANGE MEMBRANE FUEL CELL DENGAN BEBAN DINAMIS - Muhammad Faqih Alfalah; Waru Djuriatno; Tri Nurwati (Jurnal Mahasiswa TEUB, 2023)
Fuel cells are a source of environmentally friendly energy materials because they use hydrogen gas as their main ingredient. Fuel cells themselves have various types and this research uses a type of Proton Exchange Membrane Fuel Cell which uses polymer materials as its main component to produce electrical energy. The purpose of this study is to control the flow of hydrogen gas into the fuel cell to determine the flow and volume of the hydrogen gas used and to see the output of the fuel cell in the form of voltage, load voltage and current which will later be known for the efficiency and power of the fuel cell. . This test was carried outby designing a test circuit to regulate hydrogen gas by controlling the use of valves and flow sensors controlled by Arduino Uno by looking at two different conditions, namely condition 1 (maximum hydrogen gas pressure (1.5 bar)) and condition 2 (stable hydrogen gas (1.1 – 1.3 bar)). In this test, the voltage, load voltage, volume, flow and current are recorded. Based on the test results in condition 1, the value of voltage, volume and flow is higher than condition 2 and for load voltage, the more load used, the lower the value, while the more load used, the higher the value. Based on the results of the tests that have been carried out,the calculations were carried out and it was concluded that the power is directly proportional to the load used and the fuel cell has an efficiency of 58-60%. Keywords: Fuel Cell, PEMFC, Hydrogen Gas, pressure condition, voltage